Hydrodynamics study of the modified rotating disc contactor for CO2 absorption from natural gas using emulsion liquid membrane - Bhatti, I. (Institution of Chemical Engineers, 2016)
This study modified the rotating disc contactor (RDC) structure to optimize its performance for CO2 separation from natural gas feed using stable emulsion liquid membrane (ELM). Based on parametric study of absorption of CO2 from natural gas feed into ELM, the mass transfer behavior in the RDC system was optimized. Rotor diameter, stator inner diameter, and minimum free area of RDC were modified to achieve maximum contact between dispersed liquid phase and gas feed phase, which was necessary to achieve maximum mass transfer. The problem of rupture of the emulsion droplet due to pressure created by direct dispersion of gas at the bottom of conventional RDC extraction system was addressed by adding an impeller at the bottom compartment of RDC. The impeller provided continuous mixing of emulsion and a gas sparger was fitted along the impeller's side that maintained the dispersed aqueous phase miscible in system. The hydrodynamic behavior of a modified RDC was optimized for CO2 absorption from natural gas in ELM, which indicated that modified design dimensions can provide a maximum liquid-gas contact. Beside the concentration of CO2 in natural gas feed, it was observed that the speed of RDC and run time significantly influence CO2 absorption from natural gas using ELM. When all the parameters optimized for CO2 absorption from natural gas feed this study is useful in extending the application of RDC in liquid-gas system. In this study, the use of ELM in RDC can be effective for CO2 when applied under proper conditions.